Endowment Sukuk (Shares) to Finance Scientific Services in Universities (A Comparative law Study) - Eid Bleek, Adel Abdel-Fadel (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The endowment was one of the most important means of scientific, intellectual and cultural progress for the Islamic countries throughout the years of our civilization; as it contributed to building the edifices of science and culture, and publishing them through mosques, schools, institutes and libraries. A large group of scholars, innovators, and researchers graduated from these endowment scientific institutions in various branches of human and cultural knowledge. Today, the endowment plays a prominent leading role in the scientific renaissance and knowledge advancement in the Islamic society. Also, many universities in Islamic and non-Islamic countries rely on the endowment to finance their scientific and research activities, and to raise the level of their research, researchers, and graduates. This study aims to clarify the importance of endowment Sukuk to provide cash liquidity for educational services, and to provide the necessary tools for these services, and the possibility of providing scientific competencies specialized in the various fields of teaching and scientific research, to contribute to scientific and social progress. This research study also combines the deductive and inductive approaches, in addition to following the comparative jurisprudential research methodology, by studying, analyzing and deducing in the light of the writings of scholars and researchers.